What is Happening from Behind? : Making the Impact of Internet Topology Visible - Matthias Wählisch and Thomas Schmidt and Waldemar Spät (TERENA, 2008)
The Internet topology has evolved over the past decades in an evolutionary process and continues to grow. Recently, it has attracted much attention from the networking and physics communities, as it forms a unique operational instance of a planetary-scale network environment. Several measurement projects observing the Internet have been undertaken over the past years, out of which Skitter and Dimes have established as continuous recordings of the vivid process of network formation. In this paper we compare Internet measurement data obtained from Skitter and Dimes by analyzing the Internet evolution, its degree distributions and correlations at IP node level. This comparative analysis was enabled by a data conversion and processing tool-chain implemented as an extension to the BRITE topology generator which we introduce, as well. Our results show significant differences in higher nodal degrees. Correlation analysis indicates that DIMES scans discover Internet links to a fairly uniform degree, while parts remain invisible within Skitter data. Mid-range, oscillating autocorrelations are discovered as a signature of memory effects in Internet topology. Further on we analyze implications of the Internet structure as attained in both, its core and edge vicinities, for mobility management and mobile multicast routing performance.